The Effectiveness of Loving Massage on Sleep Quality in Third Trimester Pregnant Women at PMB Deliana, Marpoyan Damai District, Pekanbaru City - Intan Widya Sari; Rina Yulviana (Journal of Midwifery and Nursing, 2021)
Pregnancy is a period of crisis in a woman's life process. The period when changes occur in all body systems, including cardiovascular, respiratory, hormonal, gastrointestinal, and musculoskletal systems. Pregnant women during pregnancy experience physical and psychological changes that can cause discomfort from the first to third trimesters, one of which is sleep disturbances. One of the non-pharmacological techniques that can be given to overcome sleep difficulties in pregnant women includes relaxation techniques such as loving massage. The purpose of this study was to determine the effectiveness of loving massage on sleep quality in third trimester pregnant women. The type of research carried out was a Quasi experimental which was carried out on 03-17 October 2020 which was conducted at PMB Deliana Pekanbaru City. The population and samples used were all pregnant women who visited in October 2020. The results obtained a value of p = 0.000, so it was concluded that there was an effect of Loving Massage on the sleep quality of pregnant women in the third trimester (p <0.000). It is hoped that the next research will be able to carry out different interventions to deal with discomfort in pregnant women.